THE AGREEMENT OF SELECTED PERIPHERAL BLOOD CELL PARAMETERS BETWEEN THE AUTOMATED HEMATOLOGY ANALYZERS DXH 900 AND XN 10 AT NATIONAL INSTITUTE OF HEMATOLOGY AND BLOOD TRANSFUSION (Vietnam Journal of Community Medicine, 2026)
Objectives: Comparison of the results of Several Peripheral Blood Cell Analysis Tests on the DXH 900 and XN-10 automated hematology system at the National Institute of Hematology and Blood Transfusion in 2025.Methods: A cross-sectional method. 80 blood specimens. Samples were analyzed on both DxH 900 and XN 10 analyzers to compare white blood cell count (WBC), platelet count (PLT), red blood cell count (RBC), hemoglobin (HGB), and mean corpuscular volume (MCV), following the CLSI EP09-C guidelines.Results: All evaluated parameters (WBC, PLT, RBC, HGB, and MCV) demonstrated strong correlation (R > 0.99). Outcome A was observed for PLT (bias −2.4%) and RBC (bias 0.1%) between the two analyzers. Outcome B was identified for WBC (bias −2.0%), HGB (bias 3.4%), and MCV (bias 0.6%). Intraclass correlation coefficients (ICC) for all parameters exceeded 0.9.Conclusion: The WBC, PLT, RBC, HGB, and MCV tests performed on the DXH 900 and XN 10 analyzers demonstrated good agreement.
Keywords: Comparison, correlation, bias, CLSI EP09-C.